Bioactive Composite Cryogels Based on Poly (Vinyl Alcohol) and a Polymacrolactone as Tissue Engineering Scaffolds: In Vitro and In Vivo Studies - Bianca-; Gianina Dodi; Ioannis Gardikiotis; Vera Balan; Isabella Nacu; Iuliana Stoica; Elena Stoleru; Alina Gabriela Rusu; Alina Ghilan; Loredana Elena Nita; Aurica P. Chiriac (MDPI AG, 2023)
In light of the increasing resistance of pathogenic microorganisms to the action of antibiotics, essential oils extracted from plants with therapeutic activity provide a significant alternative to obtaining dressings for the treatment of skin wounds. The encapsulation of essential oils in an amphiphilic gel network allows better dispersion and preservation of hydrophobic bioactive substances while promoting their prolonged release. In this study, we focused on the development of a poly (vinyl alcohol) (PVA)/poly (ethylene brassylate-co-squaric acid) (PEBSA) platform embedded with thymol (Thy), and α-tocopherol (α-Tcp) as a co-drug structure with prospective use for the treatment and healing of skin wounds. The new complex bioactive system was prepared through repeated freeze-thaw processes. The influence of the composition on surface topography, hydrophilic/hydrophobic character, and in vitro interaction with simulated body fluids was evidenced. BALB/3T3 fibroblast cell culture demonstrated the cryogel scaffolds' cytocompatibility. Tests on Wistar rats confirmed their biocompatibility, integration with host tissue, and the absence of inflammatory processes. The bioactive compound significantly enhanced the healing process of full-thickness excision wounds in a rat model. Further investigations on in vivo infection models would assess the potential of the PVA/PEBSA platform with dual bioactive activity for clinical antimicrobial and wound healing therapy.